An Investigation of Links Between Transport Choices and Health: A Case Study in the UAE - AlQahtani, Mohamed Tarish (2019)
A Master of Science thesis in Civil Engineering by Mohamed Tarish AlQahtani entitled, “An Investigation of Links Between Transport Choices and Health: A Case Study in the UAE”, submitted in April 2019. Thesis advisor is Dr. Ghassan Abu-Lebdeh. Soft and hard copy available.